Lateral Load Response Of Two Identical Bridge Column-Foundation Systems In Warm And Cold Conditions - Muhannad T. Suleiman (Deep Foundations Institute, 2006)
Temperatures below freezing significantly enhance the soil shear strength and stiffness and to a lesser extent increase the compressive strength of concrete as well as the yield and ultimate strength of reinforcing steel. Consequently, the lateral load resistance of bridge columns supported by drilled shafts becomes dependent on seasonal weather conditions. To investigate the effects of seasonal freezing on the behavior of bridge columns supported by drilled shafts, large-scale field lateral load tests were conducted at 23°C (73.4°F) and -10°C (14°F) on two identical units at an field test site, which consisted of glacial till soil classified as low plastic clay. The bridge column-drilled shaft systems were subjected to cyclic lateral load with the maximum lateral column top displacements reaching approximately ±30 cm (±11.8 in.). The soil at the test site was characterized at different temperatures using unconfined compression tests in the laboratory as well as in-situ Cone Penetration and Pressuremeter Tests. Using these test results, the lateral load behavior of the column-drilled shaft systems were analyzed utilizing numerical models that consisted of beam elements representing the concrete column and the shaft and lateral springs representing nonlinear p-y response of soil. This paper focuses on comparing the calculated responses of test units with different p-y curves that were developed for the soil near the ground surface using the laboratory and in-situ tests. From the experimental study, the response of the unit tested at -10°C (14°F) was found to show 44% increase in lateral force resistance and 0.84 m (2.76 ft) upward shift of the maximum moment location compared to the response of the identical unit tested at 23°C (73.4°F). Theoretical behavior that included the temperature effects on soil, concrete and steel properties provided good correlation with the measured responses when the soil near the ground surface was modeled using the unconfined compression test or the Cone Penetration Test data, but not the Pressuremeter test data.